Analysis of Managerial Gaps in the Transformation of the Deep Learning Ecosystem in Elementary Schools - Fitri Oktafiyana; Yeni Yuniarti; Dede Trie Kurniawan (Jurnal Educative: Journal of Educational Studies, 2025)
In the context of twenty-first-century education, deep learning has emerged as a central paradigm that emphasizes conceptual understanding, critical thinking, and collaboration. Although it is theoretically acknowledged as a pedagogical ecosystem that requires strong managerial support, its implementation in elementary schools remains largely constrained by administrative-oriented management practices. This study aims to examine the managerial gaps that hinder the effective implementation of deep learning in elementary schools and to identify strategic requirements for its systematic strengthening. Employing an Integrative Literature Review (ILR) approach, this study synthesizes 20 selected scholarly articles published between 2020 and 2025 and sourced from the Google Scholar and ScienceDirect databases. Data were analyzed through thematic content analysis to generate a comprehensive conceptual synthesis. The findings reveal four major challenges, namely misalignment of strategic direction, limited managerial readiness, weak instructional leadership, and an underdeveloped culture of collaboration within schools. This study contributes theoretically by proposing a conceptual framework that connects managerial dimensions with the success of deep learning implementation, while also offering strategic implications for school leaders to shift from an administrative focus toward leadership practices that actively support the quality of learning.